Experimental analysis of MIPL based mobile IPv6 using single vs dual interface with practical test-beds - Uddin, Mohammad Moshee; Pathan, Al-Sakib Khan; Ahmed, Mohiuddin; Haseeb, Shariq (Indian Journals, India, 2011)
In this work, we have done a comprehensive study of dual interfaces on a practical test-bed to find out the effectiveness of dual interfaces. We have implemented an MIPL based test-bed to study the QoS (Quality of Service) parameters which affect mobile nodes and are considered to be of paramount importance in real time application running on MIPv6 mobile nodes. The hand-off latency, packet loss, data throughput and jitters are the parameters we have considered in this research work. We have also studied a vertical handover with the help of the test-bed to analyze handoff latency and packet loss. The vertical handover has been considered between Ethernet and Wi-Fi network access. We have analyzed the performance during MN’s handover across the networks. The results show that such type of setting could be used in various practical-oriented consumer applications that need to have mobility feature of nodes. Alongside presenting our experimental findings, we also show a comparison of performance between dual interfaces and single interface on a mobile node.